Akibat Hukum Bagi Pemegang Hak Bekas Eigendom Verponding dalam Sengketa Kepemilikan Tanah - Ahlanissa, Mellyana Putri; Aidi, Zil (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Eigendom verponding is a right to land ownership whose rights must be adjusted through the conversion provisions of the UUPA. The implementation of the conversion was given a period of time until September 24, 1980. In practice, there was still recognition of ownership of the formerland eigendom verponding which later resulted in a dispute over the land. For example, the acknowledgment of ownership of the former eigendom verponding in decision number 19/Pdt.G/2019/PN.Slw and decision number 30/Pdt.G/2019/PN.Unr. The formulation of the problem in the research: 1. What is the legal status of the formerland eigendom verponding which has not been converted according to the laws and regulations? 2. What are the legal consequences for holders of ex-rights eigendom verponding that are not converted in land ownership disputes? The approach method used is qualitative with the type of normative legal research. The main data source comes from secondary data which is also interviewed as supporting data. Secondary data sources are divided into primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques using library research and field studies in the form of interviews.